PREVALENCE AND PATTERN OF UTERINE BLEEDING AMONG BREASTFEEDING WOMEN USING PROGESTERONE-ONLY PILLS - Ratrikaningtyas, Prima Dhewi; Rosdiana, Dian; Wilopo, Siswanto Agus (YCAB Publisher & IAKMI SULTRA, 2018)
Background: Progesterone-Only Pill (POPs) is one of the ideal oral contraceptive methods for breastfeeding women. Discontinuation of POPs was mostly due to bleeding pattern disorders.Objective: The purpose of this study is to identify the prevalence and pattern of uterine bleeding on breastfeeding women using contraceptive pills containing progesterone derivatives.Methods: This study is a double blind block randomized controlled trial for the treatment group (levonorgestrel or lynestrenol pills) and non-randomized controlled trial for the control group, 6-8 weeks' postpartum women, 20 to 35-year-old, and breastfeeding. Monthly follow up was done for 6 months. Analysis was done using survival analysis, X2,and Cox's Proportional Hazard.Results: A hundred and seven women were involved with a drop-out rate of 17.8%. Subjects characteristics were â‰¤ 32-year-old, multiparous, ever used contraception with birth spacing of >60 months. Spotting and amenorrhea was the most common pattern. Levonorgestrel causes bleeding/menstrual resumption sooner in breastfeeding women than Lynestrenol.Conclusion: The most common uterine bleeding on women using Progesterone-only Pills were spotting and amenorrhea. By recognizing such effects, for Indonesian women, POPs was expected to be produced in the country and can be included in the national family planning programs.